Strategi Kebahasaan dalam Iklan Pariwisata Indonesia: Analisis Pragmatik Multimodal terhadap Pengembangan Destinasi Wisata - Fajrin, Verawati Fajrin; Fauzi, Aziz; Siti Aminataz Zuhriyah (UNIVERSITAS ISLAM SYEKH - YUSUF TANGERANG, 2026)
Digital tourism advertising not only functions as a medium for conveying information, but also as a means of building the image of the destination through the integration of various modes of communication. This research aims to analyze linguistic strategies in Indonesian tourism advertising through a multimodal pragmatic perspective and explain its contribution to the development of tourist destinations. The study uses a descriptive qualitative approach with a multimodal pragmatic analysis of eight Indonesian tourism advertising posters published through Instagram social media. Data were analyzed using Miles, Huberman, and Saldaña's interactive model which included data reduction, data presentation, and conclusion drawn. The results of the study show that linguistic strategies are built through the integration of verbal and visual elements that complement each other in producing pragmatic meanings. The verbal element functions to build the identity of the destination, provide information, and direct the audience's actions, while the visual element plays a role in strengthening, validating, and clarifying verbal messages through the representation of landscapes, tourist activities, and destination icons. The interaction of the two elements produces implications regarding beauty, uniqueness, safety, and tourist experience without having to be explicitly stated. In addition, this study found a tendency to shift promotional strategies from destination-oriented promotion to experience-oriented promotion, which is promotion that emphasizes the tourist experience more than just introducing the location. The findings show that the effectiveness of digital tourism promotion depends on the ability to integrate linguistic and visual strategies in building a positive image of the destination and encouraging tourist interest.